A corpus linguistic approach to literary language and characterization : Virginia Woolf's The Waves - Balossi, Giuseppina (Linguistic approaches to literature., 2014)
This book focuses on computer methodologies as a way of investigating language and character in literary texts. Both theoretical and practical, it surveys investigations into characterization in literary linguistics and personality in social psychology, before carrying out a computational analysis of Virginia Woolf's experimental novel The Waves. Frequencies of grammatical and semantic categories in the language of the six speaking characters are analyzed using Wmatrix software developed by UCREL at Lancaster University. The quantitative analysis is supplemented by a qualitative analysis into recurring patterns of metaphor. The author concludes that these analyses successfully differentiate all six characters, both synchronically and diachronically, and claims that this methodology is also applicable to the study of personality in non-literary language. The book, written in a clear and accessible style, will be of interest to post-graduate students and academics in linguistics, stylistics, literary studies, psychology and also computational approaches